Food supply chains and social change in the Global South : a case study of a Swedish food retailer - Hegselmann, Marius (SLU/Dept. of Urban and Rural Development, 2019)
Corporations have used the concept of Corporate Social Responsibility (CSR) for many years. The literature around CSR is viewing it from a very critical perspective, due to its connection to marketing activities from corporations. Despite the attempts to improve the image of a brand, the literature also acknowledges positive effects, like improved work safety measures, from CSR. However, one crucial question to answer is, does the CSR work of corporations contribute to improving the economic and social situation and does it help to create an equal power balance between buyer and supplier? This study looks at the Swedish food retailer Axfood and how it works with CSR in its food supply chain. Due to globalisation and more product variety in stores the food supply chain is getting longer and therefore, it is interesting to under-stand how Axfood is trying to increase their control over it in order to achieve their own sustainability goals. To analyse the work of Axfood, I used qualitative and quan-titative methods. The findings show that Axfood is using an audit system in the sup-ply chain to enforce its code of conduct and to control its suppliers. Despite the pos-itive effects for Axfood, we can find different opinions about this audit system. Therefore this thesis discussed the audit system and its effect on suppliers in the global south. This thesis discovered a power imbalance between the global south sup-plier and western buyer. One of the main issues is that local voices are not considered when a western corporation sets its sustainability policies which contribute to the above-mentioned power imbalance. A more bottom approach is needed to use the full potential of CSR.